1999
DOI: 10.1044/1058-0360.0804.319
|View full text |Cite
|
Sign up to set email alerts
|

Widening Access to Electropalatography for Children With Persistent Sound System Disorders

Abstract: Previous studies have demonstrated the value of using electropalatography (EPG) to assess, diagnose, and treat persistent sound system disorders in children. However, the application of EPG research has been limited in clinical contexts because most speech-language pathologists do not have access to the technique. This article provides an overview of recent EPG research on persistent sound system disorders and describes a network that has been established to widen access to EPG. The use of EPG via the network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…A study using electropalatography (EPG) by Houston (2002) found that almost two thirds of a group of children with cleft palate produced /n/ at a significantly more forward placement compared to /t/. Other EPG studies have found similar patterns of retracted placement for oral stops but normal alveolar placement for the nasal stop in school aged children with functional Tongue palate contact for alveolars 2 articulation disorders (Gibbon, Dent and Hardcastle, 1993;Gibbon, Stewart, Hardcastle and Crampin, 1999).…”
Section: Introductionmentioning
confidence: 78%
“…A study using electropalatography (EPG) by Houston (2002) found that almost two thirds of a group of children with cleft palate produced /n/ at a significantly more forward placement compared to /t/. Other EPG studies have found similar patterns of retracted placement for oral stops but normal alveolar placement for the nasal stop in school aged children with functional Tongue palate contact for alveolars 2 articulation disorders (Gibbon, Dent and Hardcastle, 1993;Gibbon, Stewart, Hardcastle and Crampin, 1999).…”
Section: Introductionmentioning
confidence: 78%
“…The children presented in the different studies have difficulty with fricatives, affricates, rhotic /r/, alveolar and velar phonemes (McAuliffe & Cornwell, 2008;Gibbon, Stewart, Hardcastle & Crampin, 1999;Gibbon & Wood, 2003;Carter & Edwards, 2004). Most research used case studies; however, there are different EPG systems employed in the different studies, different intervention protocols and procedures used in the studies.…”
mentioning
confidence: 99%
“…3(1), June 2015 The term is commonly used to refer to children who fail to develop their speech sounds at a typical age in the absence of an organic impairment (Gibbon, Stewart, Hardcastle & Crampin, 1999). As reported on the ASHA Portal (2015), Law, Boyle, Harris, Harkness, & Nye (2000) completed a systematic review and estimated the prevalence of speech sound disorders to range from 2% to 25% of children ages 5 to 7 years.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Various technologies, such as ultrasound and electropalatography, have been used to provide real-time information about the location and movements of the articulators during speech (e.g., Adler-Bock, Bernhardt, Gick, & Bacsfalvi, 2007;Gibbon, Stewart, Hardcastle, & Crampin, 1999;McAllister Byun, Hitchcock, & Swartz, 2014;Preston et al, 2013Preston et al, , 2014. Another alternative is visual-acoustic biofeedback, such as a dynamic visual display of the formants or resonant frequencies of the vocal tract.…”
mentioning
confidence: 99%